12Epi -9deacetoxyxenicin, new cytotoxic diterpenoid from a Bornean soft coral Xenia sp - Phan, Chin Soon; Takashi Kamada; Takahiro, Ishii; Toshiyuki Hamada; Charles Santhanaraju Vairappan (2019)
One new compound, 12-epi-9-deacetoxyxenicin (1) along with a hydroperoxide product, 12-epi-9-deacetoxy-8-hydroperoxyxenicin (2) and two known sesquiterpenoids (3–4) were isolated from a population of Bornean soft coral Xenia sp. The structures of these secondary metabolites were elucidated based on their spectroscopic data. Compounds 1 and 2 showed cytotoxic activity against ATL cell line, S1T. In addition, compound 3 exhibited hyphal inhibition of Lagenidium thermophilum.